HOSPITAL ADMISSION: A COMPREHENSIVE OVERVIEW (International Conference on Economics, Finance, Banking and Management, 2025)
Hospital admission is a critical component of modern healthcare, serving as a gateway to diagnostic, therapeutic, and rehabilitative services. This article provides an overview of the patterns, causes, and consequences of hospital admissions, with a focus on medical, demographic, and systemic factors influencing admission rates. Trends in emergency versus elective admissions, the role of chronic disease, and the impact of health system design are also discussed. Understanding these elements is essential for optimizing healthcare delivery and improving patient outcomes.